Redescription of Varipes (Ephemeroptera: Baetidae), with the Description of New Species from Bolivia and Argentina - Nieto Peñalver, María Carolina (2010)
The adult stage of the genus Varipes is described for the first time. Varipes cajuato sp. n. from Bolivia, Varipes minutus sp. n. and Varipes singuil sp. n. from Argentina are described and illustrated. The description of the first species is based on nymphs, the second on nymph and male and female subimagos and the third on nymph and male imago. A key to separate the nymphs of all the known species of the genus is included. The genus is redefined based on the type material of V. lasiobrachius and the new material available.